TEORI RI’ÂYAH AL-MASLAHAH ÂT-TUFI DAN APLIKASINYA DALAM MENAKAR PROBLEMATIKA IHDAD - Milati, Arifah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
Ri’a>yah al-maslahah is the purpose of the law. This theory by Najm ad-Di>n at-Tu>fi> serve as the first legal considerations in mu’a>malah. Maslahah considered independent without the support of certain nas even though its meaning is contained in the passages. The theory is clearly different from the theory of the clergy in general. One of the standard system of rules of classical fiqh books to the book of contemporary jurisprudence is ihda>d. The concept is unique and has been codified in the books of fiqh seems to be the dogmatic rules of grammar can not be questioned over its validity. The concept ihda>d has been standardized and codified the scholars in their books, the case is not a serious problem when associated with the position of women in the previous era, but if you do a how to find a solution as a meeting point in order to avoid collisions between the ideas that have been classical scholars formulated with the real conditions of life of modern women in the public sector. [Ri’a>yah al-maslahah adalah tujuan hukum. Teori ini oleh Najm ad-Di>n at-Tu>fi> dijadikan sebagai pertimbangan hukum pertama dalam bidang mu’a>malah. Maslahah dianggap independen tanpa didukung nas tertentu walaupun maknanya sudah terkandung di dalam nas. Teori tersebut jelasberbeda dengan teori ulama pada umumnya. Salah satu aturan sistem yang baku dari kitab-kitab fikih klasik hingga kitab fikih kontemporer adalah ihda>d. Konsep yang khas dan sudah dikodifikasi dalam kitab-kitab fikih sepertinya merupakan tata aturan dogmatik yang tidak bisa dipertanyakanulang validitasnya. Konsep ihda>d telah dibakukan dan dikodifikasikan para ulama dalam kitabkitabnya, kasus tersebut tidak menjadi problem serius bila dikaitkan dengan posisi perempuan pada era terdahulu, namun jika demikian adanya bagaimana mencari solusi sebagai titik temu agar tidak terjadi benturan antara ide yang telah dirumuskan para ulama klasik dengan kondisi riil berupakehidupan perempuan modern di sektor publik.]